The finite element analysis of convection heat transfer - Burness, Bruce Peter (Department of Mechanical Engineering, 2016)
This thesis reviews the development and current methods of numerical convection heat transfer from available literature, encompassing an analysis of the various finite element formulations available for investigating convection. It further describes the finite element formulation for the primitive variable convection heat transfer equations via a Galerkin weighted residual scheme and using mixed interpolation, and it demonstrates the capability of this method by means of five practical examples, namely natural convection in a thermally driven square cavity, a thermally driven vertical slot, a thermally driven triangular cavity, and a liquid convective diode, and forced convection in a cooling pond. This study also provides the background and framework for the problem of transient convection heat transfer, and for further steady-state studies using parameters outside those considered herein.